A Study about the Performance of Tuticorin Port Trust - Wilson, M. (Indian Journal of Marketing, 2004)
Ports are the arterial nodes of a country's industrial and economic development. They serve as the hub of the transport system, designed to facilitate both, coastal and foreign trade. Indian ports handle more than 90 percent of the Trade by volume and 70 percent by value. Ports in India are officially categorized as major ports and minor ports. A major port is a place where ships can come close to the wharf and directly load/unload the cargo to the wharf. In a minor port, a cargo would be handled at the anchorage only by engaging liters/sailing boats. India has 13 major ports and 131 minor ports (of which 14B are operational), for India's coastline stretches to nearly 5,500 km.Tuticorin has been a center for maritime trade and pearl fishery for more than 2000 years. The natural harbor with a rich hinder-land activated (he development of the port. Tuticorin was declared as a minor anchorage in 1868, and since then there have been various developments over the years. The Government of India declared Tuticorin port as the 10th Indian major port on 11th July1974. It plays a significant role in the import from and exports of goods to foreign countries.